2016
DOI: 10.3390/md14080149
|View full text |Cite
|
Sign up to set email alerts
|

The Algal Meroterpene 11-Hydroxy-1′-O-Methylamentadione Ameloriates Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: Inflammatory bowel disease (IBD) is a complex class of immune disorders. Unfortunately, a treatment for total remission has not yet been found, while the use of natural product-based therapies has emerged as a promising intervention. The present study was aimed to investigate the anti-inflammatory effects of the algal meroterpene 11-hydroxy-1′-O-methylamentadione (AMT-E) in a murine model of dextran sodium sulphate (DSS)-induced colitis. AMT-E was orally administered daily (1, 10, and 20 mg/kg animal) to DSS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Overall, the AMTs 1 and 2 were the most potent inhibitors of the production of the three pro-inflammatory cytokines, causing decreases in the range 71.20%-84.43% at 8 µg/mL; at this concentration, compound 2 also significantly inhibited COX-2 and iNOS. The inhibitory effects observed for this molecule (compound 2, also 11-hydroxy-1 -O-methylamentadione or AMT-E) on THP-1 cells are consistent with the in vivo study described in our previous report, which showed exerting intestinal anti-inflammatory activity in colitis by down-regulating TNF-α, IL-1ß, and IL-10, as well as suppressing COX-2 and iNOS expression in the mouse colon tissue [46].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the AMTs 1 and 2 were the most potent inhibitors of the production of the three pro-inflammatory cytokines, causing decreases in the range 71.20%-84.43% at 8 µg/mL; at this concentration, compound 2 also significantly inhibited COX-2 and iNOS. The inhibitory effects observed for this molecule (compound 2, also 11-hydroxy-1 -O-methylamentadione or AMT-E) on THP-1 cells are consistent with the in vivo study described in our previous report, which showed exerting intestinal anti-inflammatory activity in colitis by down-regulating TNF-α, IL-1ß, and IL-10, as well as suppressing COX-2 and iNOS expression in the mouse colon tissue [46].…”
Section: Discussionsupporting
confidence: 91%
“…325 Known brown algal-derived meroterpenes have been the focus of several biological studies with atomaric acid active against Leishmania amazonensis, 326 sargaquinoic and sargahydroquinoic acids possessing anti-adipogenic and proosteoblastogenic activities 327 and 11-hydroxy-1 0 -O-methylamentadione reducing the effect of dextran sulfate-induced colitis in mice. 328 Dolastane diterpenes from Canistrocarpus cervicornis inhibited HIV-1, 329 and spartane diterpenes from Stoechospermum marginatum induced apoptosis in melanoma cells. 330 The rst total synthesis of dictyoxetane 331,332 and the unnatural enantiomer (À)-erogorgiaene, 333 were reported.…”
Section: Brown Algaementioning
confidence: 99%
“…Ulcerative colitis (UC) is a type of inflammatory bowel disease (IBD) [ 1 ] which is a non-specific chronic inflammation of the intestine including immune disorders, genetic predisposition, environmental factors, and certain lifestyle deprivations [ 2 , 3 , 4 ]. Common clinical symptoms are weight loss, abdominal pain, diarrhoea, and hematochezia.…”
Section: Introductionmentioning
confidence: 99%